Genetic evaluation of Locus of enterocyte effacement pathogenicity island (LEE) in Enteropathogenic Escherichia coli isolates (EPEC) - Mohammadzadeh, Mohammad (Iran J Microbiol, 2013)
BACKGROUND AND OBJECTIVES: Enteropathogenic Escherichia coli (EPEC) divided into two groups typical and atypical (aspect). The main virulence genes are located in a pathogenicity island called LEE (Locus of Enterocyte Effacement). LEE frequently inserted in tRNA genes of selC, pheU and pheV in the bacterial chromosome. tEPEC and aEPEC strains have some differences in their pathogenicity. The purpose of this was to investigate the possible differences between tEPEC and aEPEC strains according to the virulence genes encoding by LEE and their relation to insertion sites. MATERIALS AND METHODS: In this study 130 E. coli isolates confirmed by biochemical analysis from diarrheal patients, were evaluated for EPEC pathotype by PCR. All EPEC strains tested for presence of some LEE encoded virulence genes and sites of LEE insertion by PCR method. RESULTS: Among 50 strains of EPEC 28 (56%) and 22 (44%) were typical and atypical strains respectively. 19 strains (30%) showed insertion in selC, 7 (14%) in pheU, 4 (8%) in pheV, 8 (16%) in pheU and pheV, 1 (2%) in selC and pheU, 6 (12%) in pheV, pheU and selC and 5 (10%) had no insertion in these sites. Moreover, spa (n = 8, 16%), espB (n = 16, 32%), espD (n = 18, 36%), espF (n = 8, 16%), espG (n = 13, 26%), espH (n = 12, 24%), map (n = 11, 32%) and tir (n = 4, 8%) were present among the strains. CONCLUSION: Results showed that most of the virulence genes are present in tEPEC isolates. However, aEPEC isolates may acquire other virulence factors. The majority of tEPEC strains showed insertion at selC and aEPEC strains in pheV and pheU.